The Effect of Financial Literacy and Locus of Control on Student’s Financial Management Mediated by Lifestyle - Hidayanti, Ika; Jihadi, Muhammad; Satiti, Novita Ratna (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to determine whether financial literacy and locus of control influence student financial management with lifestyle as the mediating effect. The population in this study were 2019-2020 class management students at the University of Muhammadiyah Malang with a total sample of 100 students. The research method uses a questionnaire with data collection techniques using questionnaires, data measurement techniques using a Likert scale and analysis using the SmartPLS 4 program. The results of the data analysis show that financial literacy has a positive and significant effect on student financial management, and locus of control has a significant positive effect on student finance. Lifestyle has a positive and significant influence on financial management. Lifestyle cannot mediate financial literacy in student financial management, but it can mediate locus of control.